Modulation of outer bank erosion by slump blocks: Disentangling the protective and destructive role of failed material on the three‐dimensional flow structure. Issue 24 (19th December 2015) - Hackney, Christopher; Best, Jim; Leyland, Julian; Darby, Stephen E.; Parsons, Daniel; Aalto, Rolf; Nicholas, Andrew
Abstract: The three‐dimensional flow field near the banks of alluvial channels is the primary factor controlling rates of bank erosion. Although submerged slump blocks and associated large‐scale bank roughness elements have both previously been proposed to divert flow away from the bank, direct observations of the interaction between eroded bank material and the 3‐D flow field are lacking. Here we use observations from multibeam echo sounding, terrestrial laser scanning, and acoustic Doppler current profiling to quantify, for the first time, the influence of submerged slump blocks on the near‐bank flow field. In contrast to previous research emphasizing their influence on flow diversion away from the bank, we show that slump blocks may also deflect flow onto the bank, thereby increasing local shear stresses and rates of erosion. We use our measurements to propose a conceptual model for how submerged slump blocks interact with the flow field to modulate bank erosion. Key Points: Submerged blocks of eroded bank material directly affect the 3‐D near‐bank flow field Submerged slump blocks may deflect flow onto the bank A new conceptual model of bank erosion accounts for the influence of submerged slump blocks